Epidemiology of National Football League training camp injuries from 1998 to 2007 - Feeley, B. T.; Kennelly, S.; Barnes, R. P.; Muller, M. S.; Kelly, B. T.; Rodeo, S. A.; Warren, R. F. (The American Journal of Sports Medicine, 2008)
Football is one of the leading causes of athletic-related injuries. Injury rates and patterns of the training camp period of the National Football League are unknown.